UNDERSTANDING THE CONCEPT OF MATHEMATICAL CAPABILITIES COMPARISON BETWEEN STUDENTS LEARNING THAT LEARNED USING MIND MAPPING MODEL WITH LIVE MODEL IN CLASS VIII SMPN 3 TUNGKAL ULU - sri dewi (Jurnal Ilmiah Dikdaya, 2017)
This research is motivated by the ability of students' understanding of mathematical concepts Low. One contributing factor is the teacher's teaching style or learning model that is still in use still live where there is a tendency to minimize the involvement of students. While teachers are more active in the learning process. One model that is expected to improve students' understanding of mathematical concepts is mind mapping. Mind mapping learning model is the submission of ideas or concepts and problems in learning then discussed in small groups so that gave birth to the various alternatives to solve. This study aims to determine the ability of students understanding of mathematical concepts between that learned to use mind mapping learning model is better than the ability of students' understanding of mathematical concepts that learned by direct learning model. This study used an experimental method with quasi-experimental design (quasi research method) with a student population of SMP Negeri 3 Tungkal Ulu Academic Year 2015/2016. Sampling using random sampling and sample drawn is a class VIII D as an experimental and VIII C as the control class. From the results of research conducted average scores for the experimental class was 78,15 with a standard deviation of 12,13 and the average value of the control class was 69,23 with a standard deviation of 15,22. As well as from the hypothesis test obtained at 2,655 and 1,675 on the real level of 0,05 . From the calculation it is seen that greater than it received. Based on the final results can be concluded that the ability of students ' understanding of mathematical concepts that learned to use mind mapping learning model is better than the ability of students' understanding of mathematical concepts that learned by direct learning model in class VIII SMP Negeri 3 Tungkal Ulu. Keywords: Mathematical Capabilities Concept Training, Learning Model of Mind Mapping, Direct Learning Model